(untitled) (Web of Teachers: Inderscience Research, 2024)
At the end of the XIX century - the beginning of the XX century, the residential addresses of the inhabitants of the Guzor Principality of the Bukhara Emirate were analyzed according to the properties, and comments were made about the villages and clans of the residents. Some promising data on these issues are discussed in the article.